The Chalabi family and its social activities in Iraq 1918-1958 - Jasim, Asmaa Rahim; Hussein, Alia Mohammed (Al-Adab Journal, 2022)
The Chalabi family is one of the ancient Iraqi families that belong to the authentic Arab Tayy tribe, which has a prominent social position, and a prestige that stems from the originality of that family and its social roots, which gave it a social status in Iraq during the royal era, and the same thing made some personalities and members of the Chalabi family stand out In the social issues of concern to the Iraqi society from cooperation and helping the classes of society to solve a problem through associations that are concerned with the social aspect, as well as their councils, which had the significance of goals of a social nature characterized by the spread of intellectual and cultural awareness, and thus personalities from this family emerged in social positions in The Iraqi government, including the Ministry of Education, as well as the Syndicate of Health Professionals and others throughout the monarchy in Iraq 1921-1958 Through which some members of the Chalabi family emerged and some of them became her head and membership, and they had a great impact on it in the service of Iraqi society during that period.